The palette of Mikolа Vingranovsky landscape lyrics (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article is devoted to the study of color imagery in the poems of M. Vingranovsky. Accented on the features of the semantic shades of images-interferents, the specifics of their functioning in the poet’s landscape lyrics. The purpose of this article is to try to determine the specifics of the art semantics, which takes on color in the Mikolа Vingranovsky’s landscape lyrics.It was found that the perception and interpretation of color is a purely subjective process, the artist selection of colors in addition to fine functions performs psychoemotional impact on the reader. Nature in the poetry of the artist is a perfect and complete harmony. Therefore, reading the book of nature, the lyrical hero of Mikola Vingranovsky’s poetry of openly admires the miracle, the mysterious beauty of the world. He is emotionally contemplating reality. Intonation of sincere recognition in love for the world borders in the poetry of the artist with meditating force of the two natures, human and natural. In several poems the author convert visual images to audio and tactile and vice versa (the epithets “the shadow of sinogolos”, “green voice of the gardens is the name of a cuckoo”), forming the synesthetic design. The depth of intimate feelings of the lyrical hero more noticeable to the principle of anthropomorphism, which gives organic, expressed attitude to the natural world. In verse discharged the whole complex of personified images that form a complete picture of the autumn garden, convey the mood of the lyric hero, which coincides with the author's “I”. The motif of the garden, all dressed and adorned by human nature, present in the verbal art of various peoples and epochs (the biblical Garden of Eden, gardens Alcinoe in Homer's “Odyssey”). The colours in the poetic works of M. Vingranovsky often reveals the presence of its own semantic field that is defined by the context. So the way winter is not traditionally white and often painted in yellow or grey, sometimes more noticeable contrasting colors. Made in the article, the observations confirm the hypothesis about the presence in the poetry of M. Vingranovsky figures of synesthesia, and the concept of “nature” is represented not as a blind element, mindless palette and chaotic cacophony of sound, and how in tune with the human spiritual essence.
Keywords: coloring; color images; M. Vingranovsky; synesthesia; symbol; concept “nature”